TRANSFORMASI PELAYANAN PUBLIK BERBASIS DIGITAL DI ERA MODERNISASI DINAS KESEHATAN KOTA PROBOLINGGO - Ulva, Nourma; Annisa, Putri Aalia; Vidyanti, Sisca Ratna; Aldo, Praka; Hidayat, Robi; Kautshar, Adil Al (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2024)
Digital-based transformation of public services has become a necessity in the era of modernization, especially in the health sector. This research aims to analyze the implementation of digital systems at the Probolinggo City Health Service and its impact on the quality of services to the community. The method used is a qualitative approach with interview and observation techniques. The research results show that the application of information technology, such as online registration applications and health information systems, has increased the efficiency and transparency of services. However, challenges such as the digital divide and limited human resources still need to be overcome. In conclusion, although digital transformation brings many benefits, a comprehensive strategy is needed to ensure that all levels of society can access health services optimally.